Sociopragmatics Analysis of Politeness Strategy of the Main Character's Dialogues of Tinker Bell in Secret of the Wings Movie - Mujiono Mujiono; Avil Lailatul Ula (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2020)
This study investigated the types and functions of politeness strategy used by the main character of Tinker Bell in Secret of the Wings movie. The study was a descriptive qualitative approach. The instrument of this study was document analysis. It focused on analyzing and interpreting recorded documents. To analyze the data, four interactional procedures were applied. Triangulation was used to justify the trustworthiness of data. The findings showed that the interaction between the main character and her addressee realized all politeness strategies. There were 39 data found in the conversation. Each politeness strategy's frequency was positive politeness in the first grade, with 51.3%, followed by a bald-on record with 33.3%. Negative politeness and 'off record' were the same positions with 7.7 %, %. Second, the researchers reported two politeness strategy functions indicated by the transactional view with 74.4 % and interactional view with 25.6%. Last, the main character applied the politeness strategy to have a close relationship, know each other, and avoid the addressee's imposition. This politeness strategy had implications on using politeness strategies of a language in communication aspects for the community.